Evaluation of sustainability in university tutoring programs for educational leadership: a case study - Villarrubia Zúñiga, María Soledad; Ortiz-Jiménez, Macarena; González García, Paula; Suárez-Campos, Laura (Frontiers in Education, 2024)
University tutoring programs should aim to create a conducive environment for promoting pedagogical practices that align with the principles of Education for Sustainable Development (ESD). However, it has been observed that teachers often face difficulties when implementing ESD in tutoring sessions, such as lack of time, students’ reluctance to share personal issues, and insufficient training and resources. This research is part of a larger project that aims to study university tutoring as a pedagogical tool to identify problems affecting students’ learning processes and provide solutions to improve the quality of teaching. As participatory and dialogical models are most appropriate for promoting ESD, a well-developed tutoring model will contribute to the creation of useful pedagogical practices to guide and improve the status quo of students. Through an exploratory-descriptive study, this paper compares two university tutoring programs in Spain and Morocco to identify the most frequent issues hindering educational leadership and sustainable development, which can impact academic success.